Liver catalase activity in patients with iron deficiency anemia - Özsoylu, Şinasi (The Turkish Journal of Pediatrics, 1967)
In this study, human liver catalase activity of 36 subjects was assayed 40 times. The study showed that liver catalase activity does not decrease in patients with iron deficiency anemia and that it is neither related to the sex, age, liver pathology nor to possible serum copper deficiency in human beings.